2020
DOI: 10.1002/adem.202001061
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Mechanical Properties of Graphene Nanosheet–Reinforced Powder Metallurgy Nickel‐Based Superalloy

Abstract: Nickel-based superalloys [1] are key materials in airplane and turbine disks due to their outstanding properties such as high tensile strength and excellent creep deformation resistance. With the increasing requirements of the modern aerospace industry on the performance of materials, traditional nickel alloys are gradually unable to meet the demands of high properties. Thus, selecting the nanoreinforcement phase to construct metal matrix composites (MMCs) is one of the simple and easy ways to improve the perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…It has been reported that the perfectly constructed graphene nanoparticles are chemically stable and mostly do not react with metals (chemically). [30] It was observed that the grains interlocked through the grain boundaries, which suggests that the grains were closely packed. Hence, strong metallurgical bonding exists between the metallic elements and reinforcement (graphene).…”
Section: B Microstructure Analyses Of a Pure In738lc Alloy And Gnps-in738lc Compositesmentioning
confidence: 99%
“…It has been reported that the perfectly constructed graphene nanoparticles are chemically stable and mostly do not react with metals (chemically). [30] It was observed that the grains interlocked through the grain boundaries, which suggests that the grains were closely packed. Hence, strong metallurgical bonding exists between the metallic elements and reinforcement (graphene).…”
Section: B Microstructure Analyses Of a Pure In738lc Alloy And Gnps-in738lc Compositesmentioning
confidence: 99%
“…In particular, graphene nanosheet has excellent mechanical properties (modulus: ≈1 YPa, strength: ≈130 GPa), huge specific surface area (600–10 000) and very large width to thickness ratio (≈100), making them possessing the highest strength, best toughness and largest specific surface area found so far. [ 135,136 ] Jang et al. developed a biomimic biocomposite complexing by GO/crystalline HAP, and the results showed that the protein adhesion ability was better than pure HAP because GO had a high protein adsorption capacity by surface reactors.…”
Section: A Type Of Bone Scaffold Materials With Both Mechanical and B...mentioning
confidence: 99%
“…Thus, the constitutive equation at a strain of 0.4 was established as Equation (11), by substituting A, α, n, and Q into Equation (3) ε : ¼ 1.51  10 32 ½sinhð0.00993σÞ 3.1873 expðÀ894260=RTÞ (11)…”
Section: Determination Of Materials Parametersmentioning
confidence: 99%
“…[5] The development of P/M superalloys includes Rene 95, [6] EP741NP, [7] N18, [8] Rene 88DT, [9] RR1000, [10] and FGH96. [11] EP741NP, a P/M superalloy manufactured by direct HIP, is widely used in turbine engines. [7,[12][13][14] The main disadvantage of superalloys made by HIP is the formation of a prior particle boundary (PPB) containing oxides, carbides, and γ 0 , which is detrimental to the material's mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation